Guanine uptake and metabolism in Neurospora crassa. - Magill, C W (1982)
Guanine is transported into germinated conidia of Neurospora crassa by the general purine base transport system. Guanine uptake is inhibited by adenine and hypoxanthine but not xanthine. Guanine phosphoribosyltransferase (GPRTase) activity was demonstrated in cell extracts of wild-type germinated conidia. The Km for guanine ranged from 29 to 69 micro M in GPRTase assays; the Ki for hypoxanthine was between 50 and 75 micro M. The kinetics of guanine transport differ considerably from the kinetics of GPRTase, strongly suggesting that the rate-limiting step in guanine accumulation in conidia is not that catalyzed by GPRTase. Efflux of guanine or its metabolites appears to have little importance in the regulation of pools of guanine or guanine nucleotides since very small amounts of 14C label were excreted from wild-type conidia preloaded with [8-14C]guanine. In contrast, excretion of purine bases, hypoxanthine, xanthine, and uric acid appears to be a mechanism for regulation of adenine nucleotide pools (Sabina et al., Mol. Gen. Genet. 173:31-38, 1979). No label from exogenous [8-14C]guanine was ever found in any adenine nucleotides, nucleosides, or the base, adenine, upon high-performance liquid chromatography analysis of acid extracts from germinated conidia of wild-type of xdh-l strains. The 14C label from exogenous [8-14C]guanine was found in GMP, GDP, GTP, and the GDP sugars as well as in XMP. Xanthine and uric acid were also labeled in wild-type extracts. Similar results were obtained with xdh-l extracts except that uric acid was not present. The labeled xanthine and XMP strongly suggest the presence of guanase and xanthine phosphoribosyltransferase in germinated conidia.